Front and Back Matter for Volume 1 Issue 2, September 2024 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2024)
Volume 1, Issue 2, September 2024 This issue consists of 5 articles contributed by 12 authors affiliated with 11 affiliations from our countries including Indonesia (Universitas Pendidikan Ganesha, Sekolah Tinggi Ilmu Kesehatan Medistra Indonesia, Universitas Hindu Indonesia, Indonesian Society of Epidemiologists, One Health Laboratory Network, Universitas Hang Tuah, Universitas Padjadjaran), Australia (Monash University), Ethiopia (Jimma University, Jigjiga University), and Pakistan (University of Management and Technology Lahore).